Supramolecular Seeding-Induced Fibrillar Refinement for High Efficiency and Stable Organic Solar Cells - Shijie Liang; Zihao Gao; Qiaomei Chen; Linhu Liu; Yuwen Wang; Qin Tan; Yang Li; Christopher R. McNeill; Weiwei Li (Journal of the American Chemical Society, 2026)
Abstract Achieving optimal morphology and long-term stability in organic solar cells (OSCs) remains challenging because the donor–acceptor crystallization sequence is often poorly coordinated during solution processing. Here, we develop a supramolecular crystallization seeding strategy by introducing a hydroxyl-terminated, highly crystalline acceptor (Y–OH) into the D18/L8-BO system. By engineering a hierarchical thermodynamic compatibility gradient (χD18/Y–OH > χL8-BO/Y–OH > χD18/L8-BO), Y–OH becomes interface-active and exhibits an interfacial distribution tendency in the multicomponent film. In situ UV–vis measurements reveal that Y–OH undergoes early stage ordering on a time scale closer to the donor, thereby participating in the initial morphology evolution and steering the subsequent organization of L8-BO into a refined interpenetrating fibrillar network with reduced fibril diameters. This morphology simultaneously promotes efficient exciton harvesting/charge generation and enables balanced charge transport, leading to concurrent enhancements in short-circuit current density (JSC) and fill factor (FF). As a result, the optimized ternary devices deliver a PCE of 20.90% (vs 20.05% for the binary control). Moreover, hydroxyl-enabled supramolecular interactions provide noncovalent anchoring that retards thermally driven morphology relaxation, allowing the devices to retain ≈83% of their initial efficiency after 900 h at 65 °C. This work highlights supramolecular crystallization seeding as an effective design principle for simultaneously improving efficiency and thermal stability in OSCs.